The game between host antiviral innate immunity and immune evasion strategies of senecavirus A - A cell biological perspective - Zhao, Kuan; Zhang, Shixia; Liu, Xiaona; Guo, Xiaoran; Guo, Zhaomeng; Zhang, Xiaozhan; Yuan, Wanzhe (Frontiers in Immunology, 2022)
Innate immunity is the first line of the cellular host to defend against viral infection. Upon infection, viruses can be sensed by the cellular host’s pattern recognition receptors (PRRs), leading to the activation of the signaling cascade and the robust production of interferons (IFNs) to restrict the infection and replication of the viruses. However, numerous cunning viruses have evolved strategies to evade host innate immunity. The senecavirus A (SVA) is a newly identified member of the Picornaviridae family, causing severe vesicular or ulcerative lesions on the oral mucosa, snout, coronary bands, and hooves of pigs of different ages. During SVA infection, the cellular host will launch the innate immune response and various physiological processes to restrict SVA. In contrast, SVA has evolved several strategies to evade the porcine innate immune responses. This review focus on the underlying mechanisms employed by SVA to evade pattern recognition receptor signaling pathways, type I interferon (IFN-α/β) receptor (IFNAR) signaling pathway, interferon-stimulated genes (ISGs) and autophagy, and stress granules. Deciphering the antiviral immune evasion mechanisms by SVA will enhance our understanding of SVA’s pathogenesis and provide insights into developing antiviral strategies and improving vaccines.